BIOASSAY TECHNIQUES OF SOIL ECOLOGICAL STATUS ASSESSMENT NEAR THE AIRPORTS - Madzhd, Svitlana (Proceedings of National Aviation University (archive), 2014)
Results of biological methods of an estimation of definition of toxicity of ground in territorie sadjoining to airports are presented. It is lead quality standard of a soil cover on biotests of different trophic levels. It is certain toxicity of ground in vicinities of airports